2019
DOI: 10.1186/s12939-019-0928-z
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable populations and the right to health: lessons from the Peruvian Amazon around tuberculosis control

Abstract: Background In 2014 the World Health Organization (WHO) launched the “End TB Strategy”, setting new ambitious goals for elimination of tuberculosis (TB). In contrast with previous efforts to control TB, the new strategy adopted the protection and promotion of human rights in TB prevention and care as a core pillar. This mandated the development of national programmes that are sensitive to the characteristics of populations and responsive to structural factors that put people at increased risk of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
1
17
0
8
Order By: Relevance
“…In our study, although the older age were over presented in the bacteriologically confirmed group, after adjusted with other factors, age as well as gender were not statistically significant. Compared with state employees, the unemployed and farmers usually had disadvantage in household income and living conditions, leading them vulnerable to TB [24,25]. The vulnerability might lower their health seeking behavior or accessibility to health care, thus lead to later stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although the older age were over presented in the bacteriologically confirmed group, after adjusted with other factors, age as well as gender were not statistically significant. Compared with state employees, the unemployed and farmers usually had disadvantage in household income and living conditions, leading them vulnerable to TB [24,25]. The vulnerability might lower their health seeking behavior or accessibility to health care, thus lead to later stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with state employees, unemployed and farmers usually had disadvantage in household income and living conditions, leading them vulnerable to TB. [23,24] The vulnerability might lower their health seeking behavior or accessibility to health care, thus lead to later stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with state employees, the unemployed and farmers usually had disadvantage in household income and living conditions, leading them vulnerable to TB. [24,25] The vulnerability might lower their health seeking behavior or accessibility to health care, thus lead to later stage of the disease. As TB control program being enhanced and active TB case nding being carried out to larger population, less patients may be diagnosed at later and severe stage of the disease, as a result BC may decrease if testing strategy remain.…”
Section: Discussionmentioning
confidence: 99%